Structuring dual vocational education and training in a competence oriented manner : Aerospace occupations set in the standard - Burger, Barbara [Verfasser]; Dybowski, Gisela [Verfasser] (My University, 2009)
"The present paper reports on the MOVE PRO EUROPE pilot project conducted by the German companies involved in the European Aeronautic Defense and Space Agency (EADS) and which came to a conclusion in August. The main focus of the pilot project was on two objectives: to use the skills potentional within real work processes in a targeted way in training and to make a contribution towards the European debate surrounding competence oriented occupational standards." (Autorenreferat, BIBB-Doku)
Keywords: S 2.3.1 Modellversuche in der Berufsbildung; G 1.2.3.1 Potenziale; I 1.4 Berufsbildungsprojekte/Entwicklungsprojekte; Betriebliche Berufsausbildung; Internationales Unternehmen; Flugzeugindustrie; Arbeitsprozessorientierung; Kompetenzorientierung; Kompetenzstandards; Elektroniker für luftfahrttechnische Systeme; Modellversuch